Comparison of the effect of erector spinae plane block for postoperative analgesia on neutrophil/lymphocyte ratio and platelet/lymphocyte ratio in patients operated for breast cancer - Şahin Karadil, Kübra; Gültekin, Ahmet; Şahin, Ayhan; Özkan Gürdal, Sibel; Yıldırım, İlker and Arar, Cavidan (The European Research Journal, 2024)
Objectives: It was seen that recurrence and metastasis after breast cancer surgery are related to the immune response of the host. Anesthetic agents modulate the surgical stress response or directly impair the functions of immune system cells. In our study, we aimed to compare the effects of nonsteroidal anti-inflammatory drugs and erector spinae plane block, which are among the methods we use for postoperative analgesia, on the neutrophil/lymphocyte ratio and platelet/lymphocyte ratio in patients undergoing breast cancer surgery. Methods: One hundred female patients aged 18-75 years, scheduled for unilateral breast cancer surgery, and who agreed to participate were included in our study. These cases were divided into two groups of the analgesia method: Those with erector spinae plane block (Group E) and those who were administered nonsteroidal anti-inflammatory drugs (Group N). According to the results, preoperative and postoperative neutrophil/lymphocyte ratio and platelet/lymphocyte ratio values were calculated and recorded. Results: Neutrophil/lymphocyte ratio and platelet/lymphocyte ratio were statistically higher in both groups in the postoperative period. No statistically significant difference was found when the preoperative and postoperative measurement changes of the laboratory parameters between the groups were compared. Postoperative VAS scores were statistically significantly lower in Group E. Conclusions: We concluded that when erector spinae plane block and nonsteroidal anti-inflammatory drug use were compared in managing postoperative analgesia in breast cancer surgery, their effects on the neutrophil/lymphocyte ratio and platelet/lymphocyte ratio were not superior to each other. However, the erector spinae plane block was superior for adequate pain control.